Improving Teaching Skills of the Prospective Physical Education Teachers through Drill Guide Method - Jusuf Blegur; Andreas J. F Lumba (Universitas Pendidikan Indonesia, 2019)
This study aimed at improving the teaching skills of prospective physical education teachers by using the drill guide method. The design used was Classroom Action Research from S. Kemmis and R. McTaggart involving 41 research subjects. Data for each cycle were taken by using teaching skill observation guidelines and in-depth interviews. The data were analysed descriptively. The improvement of the subjects' teaching skills from the Pre Cycle to Cycle 1 was  86,4%, from Cycle 1 to Cycle 2 was 12,8%, and from Cycle 2 to Cycle 3  was 16,7%. The fastest improving item was to wear clean and neat clothes (3,95) and the slowest one was to relate the material to other fields of science (2,46). From the result, it can be concluded that the drill guide method is one of the best methods that can be applied when educators (lecturers or teachers) are giving a skill guidance.